Invasive Prunus serotina - a new host for Yponomeuta evonymellus (Lepidoptera: Yponomeutidae)? - Piotr KAROLEWSKI; Andrzej M. JAGODZIŃSKI; Marian J. GIERTYCH; Adrian ŁUKOWSKI; Edward BARANIAK; Jacek OLEKSYN (European Journal of Entomology, 2014)
Introduction of non-native species of plants affects the existence and feeding preferences of herbivorous insects. The bird cherry ermine moth (Yponomeuta evonymellus) is considered a typical monophagous insect, which feeds only on bird cherry (Prunus padus) leaves. However, in recent years, we have observed Y. evonymellus larvae feeding on leaves of the non-native (in Europe) and highly invasive black cherry (Prunus serotina). We hypothesized that this insect can feed on P. serotina leaves with no negative effects on its growth and development and that the main reason why it does not accept this plant as a host is the phenological difference between the two species of cherry. Moving individuals of the three larval instars (L1, L2 and L3) from bird cherry to black cherry did not affect the percentage of adults that emerged from the pupae or the masses of the moths. In addition, in one experiment, the moths were heavier and the percentage parasitized was lower on P. serotina than on P. padus. Thus, the leaves of black cherry were at least as good a food source as P. padus for Y. evonymellus. During the feeding period, there were low concentrations of defense compounds (phenolics and condensed tannins) in the leaves of both species. However, it is likely that the low success of Y. evonymellus in infesting P. serotina is due to spring frosts and heavy rains, which are deadly for larvae in an early stage of development on black cherry. In the field these weather conditions resulted in a very high mortality of larvae in our experiment. In conclusion, the use of bird cherry as a host by Y. evonymellus is mainly determined by its phenology.